Onsite Mentorship Model for Isolation and Management of Viral Hemorrhagic Fever Syndromes at a Ugandan Hospital. (October 2020) - Waitt, Peter; Nakato, Shillah; Ayebare, Rodgers; Ssekabira, Umaru; Nanyondo, Judith; Waitt, Catriona; Okoboi, Stephen; Lamorde, Mohammed
Abstract : Background: Uganda is prone to viral hemorrhagic fever (VHF) outbreaks. Infection prevention and control capacity is critical to supporting patient care, to preventing nosocomial transmission to health workers, and to limiting spread within the community. Offsite didactic training may increase healthcare worker knowledge, but this approach may be inadequate for assuring confident execution of practical clinical tasks in patient care settings. We aimed to develop a competency-based, onsite mentorship model for sentinel case isolation and management of viral hemorrhagic fever syndromes in Uganda. Methods: The Naguru Regional Referral Hospital (China Uganda Friendship Hospital) Kampala was selected as a site for training after its designation by the Uganda Ministry of Health (MoH) as facility for isolation of healthcare workers with suspected or confirmed VHF. The need for mentorships was determined from information from training providers, MoH assessments, hospital management, and key hospital staff. A list of skills was developed by reviewing WHO case management guidelines and Uganda-approved VHF trainings. The skills, exercised using scenario-based drills, focused on safety practices, identification and isolation of suspect cases, and delivery of optimized clinical care to suspected cases of VHF, among others. Trained facilitators (n = 2–4) supervised drills attended by staff from Naguru and other Kampala-based health facilities. Drills were scheduled weekly and were ordered to progressively increase in complexity. Specific drills could be repeated at the subsequent mentorship visit if gaps were identified. Results: Over 3 months, 12 drills were completed (Table 1). Cadres trained included 10 medical doctors, 12 nurses, 3 clinical officers, 5 laboratory technicians, 6 hygienists, 2 security officers, and 3 administrative officers. On average, 8 hospital staff attended weekly drills. During 3 months of the intervention, 1 suspected case of VHF and 3 cases with laboratory confirmed cholera were managed by the hospital team, and staff demonstrated the capacity for safe handling of patients with infectious bodily fluids. Barriers encountered included practice fatigue from repeated drills, challenges with team cohesion since members were from different institutions, limited personal protective equipment for repeated trainings, and competing routine hospital activities that reduced numbers of staff available for training. Repeated drills included clinical management, cadaver management, and infectious spills. Conclusions: This onsite mentorship project supported healthcare workers to gain confidence in the management of suspected VHF infection and other highly infectious diseases. Continued mentorship, hospital administration support and increase in exercise complexity are needed to consolidate on these gains. Funding: None Disclosures: Mohammed Lamorde reports contract research for Janssen Pharmaceutica, ViiV, and Mylan.